USM, SILTERRA SIGNS AGREEMENT IN MICROELECTRONICS INDUSTRY - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 11 January 2015 – Universiti Sains Malaysia (USM) today signed a collaboration agreement (CA) withSilterra Malaysia Sdn. Bhd. for the access to the Multi Project Wafer (MPW) in completing the microelectronics ecosystem at the university which comprised of designing, confirmation, fabrication, testing and measuring as well as packaging.